Algorithms, applications and Big Data, new paradigms in the process of communication and teaching-learning of data journalism - Flores Vivar, Jesús Miguel (2018)
Disruptive technologies and their impact on journalism and communication force us to assume challenges in learning new techniques for data and information processing. Interdisciplinary knowledge is evident in the teaching of new professional profiles. Data journalism is an example of this, so the immersion into a data culture must be preceded by awareness in the learning of news applications, algorithms or the treatment of Big Data, elements that configure new paradigms among journalists of the media on the Internet. With the revision of texts, direct observation of selected applications and case study, some conclusions are established that contain a growing demand in the knowledge of new techniques. The results show the use of technological resources and the proposal of changes in the curricula of the communication faculties.